Investigation of Electric Field Induced Ion Migration in Semiconductor Encapsulation Materials without the Interference of Electron Conductivity. (22nd September 2016) - Schwab, S.; Jung, J.; Gruber, S.; Bauer, M.; Miethaner, S.; Nelhiebel, M.; Hutter, H.
Abstract : Ion migration can cause severe damage to high power semiconductor devices. One of the main sources of mobile ions is the encapsulation material such as molding compounds. Within this work a method will be described to evaluate the risk of field induced ion migration of different molding compounds depending on the temperature and field strength. This method allows the qualitative and quantitative determination of ion mobility in molding compounds, without the interference of electron conductivity.